Impact of baricitinib in combination with topical steroids on atopic dermatitis symptoms, quality of life and functioning in adult patients with moderate‐to‐severe atopic dermatitis from the BREEZE‐AD7 Phase 3 randomized trial. (5th June 2021) - Wollenberg, A.; Nakahara, T.; Maari, C.; Peris, K.; Lio, P.; Augustin, M.; Silverberg, J.I.; Rueda, M.J.; DeLozier, A.M.; Pierce, E.; Yang, F.E.; Sun, L.; et al.
Abstract: Background: Baricitinib is an oral, selective, reversible Janus kinase 1/2 inhibitor approved in the European Union and Japan and under investigation in the United States for treatment of atopic dermatitis (AD). Objectives: To evaluate the impact of baricitinib plus background topical corticosteroids (TCS) on health‐related quality of life (HRQoL), how AD symptoms impact work productivity and life functioning, and treatment benefit using patient‐reported outcome (PRO) assessments in patients with moderate‐to‐severe AD previously experiencing inadequate response to TCS. Methods: Adult patients with AD in BREEZE‐AD7, a Phase 3, multicentre, double‐blind trial, were randomised 1 : 1 : 1 to daily oral placebo (control) or baricitinib 4‐ or 2‐mg plus TCS. PROs reported Week 1 through Week 16: Dermatology Life Quality Index (DLQI), Work Productivity and Activity Impairment‐AD (WPAI‐AD); Patient‐Reported Outcomes Measurement Information System (PROMIS) Itch and Sleep measures, and Patient Benefit Index (PBI). Data were analysed using logistic regression (categorical) and mixed model repeated measures (continuous). PBI scores were analysed using analysis of variance. Results: A total of 329 patients were randomised. Treatment with baricitinib 4‐mg ( N = 111) or 2 mg ( N = 109) plus TCS led to rapid, statistically significant improvements [vs. TCS plus placebo ( N = 109)] in DLQI ≥4‐point improvement starting at Week 2 (4‐mg plus TCS, P ≤ 0.001; 2‐mg plus TCS P ≤ 0.05), change from baseline in WPAI‐AD presenteeism at Week 1 (4‐mg plus TCS, P ≤ 0.01; 2‐mg plus TCS P ≤ 0.05) and PROMIS itch interference at Week 2 (4‐mg plus TCS P ≤ 0.01). Improvements were sustained through Week 16 for baricitinib 4‐mg. Statistically significant improvements were observed at Week 16 for PBI global score (4‐mg plus TCS, P ≤ 0.001; 2‐mg plus TCS P ≤ 0.05). Conclusions: Baricitinib plus TCS vs. placebo plus TCS showed significant improvements in treatment benefit at Week 16 and rapid significant improvements in HRQoL and impact of AD symptoms on work productivity and functioning through 16 weeks.